2017
DOI: 10.21608/ejbo.2017.1146
|View full text |Cite
|
Sign up to set email alerts
|

Role of Bio-Fertilizer Treatments in Alleviating the Adverse Effect of Water Stress in Mangifera indica

Abstract: ATER stress is one of the most important abiotic stresses that …….....may limit agriculture production worldwide. This work was carried out on mango trees (Mangifera indica L.) to study the effect of exposure to different levels of drought stress (65, 75, 85 and 100 % of full irrigation requirements), in addition, to evaluating the role of using some plant growth promoting rhizobacteria (PGRP); such as Azospirillum and Azotobacter, in alleviating drought-induced changes. Physiological and biochemical changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
0
0
0
Order By: Relevance
“…Drought stress signi cantly reduces the uptake of essential nutrients required for optimum plant growth and development. These results are in line with the ndings of Akhtar et al [55] and Khalil et al [73], who demonstrated a marked increase in the uptake of K, N, and P in wheat treated with SiO 2 NPs and PGPB that manifested in direct proportion to the concentration of applied SiO2 NPs. Rezakhani et al [29] also reported the concentrations of Si and P in wheat shoots after using different Si and Pseudomonas sp.…”
Section: Discussionsupporting
confidence: 92%
“…Drought stress signi cantly reduces the uptake of essential nutrients required for optimum plant growth and development. These results are in line with the ndings of Akhtar et al [55] and Khalil et al [73], who demonstrated a marked increase in the uptake of K, N, and P in wheat treated with SiO 2 NPs and PGPB that manifested in direct proportion to the concentration of applied SiO2 NPs. Rezakhani et al [29] also reported the concentrations of Si and P in wheat shoots after using different Si and Pseudomonas sp.…”
Section: Discussionsupporting
confidence: 92%